Enhancing the Selection and Performance of Working Dogs - Bray, Emily E.; Otto, Cynthia M.; Udell, Monique A. R.; Hall, Nathaniel J.; Johnston, Angie M.; MacLean, Evan L. (Frontiers in Veterinary Science, 2021)
Dogs perform a variety of integral roles in our society, engaging in work ranging from assistance (e.g. service dogs, guide dogs) and therapy to detection (e.g. search and rescue dogs, explosive detection dogs) and protection (e.g. military and law enforcement dogs). However, success in these roles, which requires dogs to meet challenging behavioral criteria and to undergo extensive training, is far from guaranteed. Therefore, enhancing the selection process is critical for the effectiveness and efficiency of working dog programs and has the potential to optimize how resources are invested in these programs, increase the number of available working dogs, and improve working dog welfare. n this paper, we review two main approaches for achieving this goal: (1) developing selection tests and criteria that can efficiently and effectively identify ideal candidates from the overall pool of candidate dogs, and (2) developing approaches to enhance performance, both at the individual and population level, via improvements in rearing, training, and breeding. We summarize key findings from the empirical literature regarding best practices for assessing, selecting, and improving working dogs, and conclude with future steps and recommendations for working dog organizations, breeders, trainers, and researchers.